2018
DOI: 10.3892/mmr.2018.9313
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive impairments induced by severe acute pancreatitis are attenuated by berberine treatment in rats

Abstract: Cognitive impairments induced by severe acute pancreatitis (SAP) are severe complications, for which there are a lack of effective pharmacological treatment strategies. Berberine is an isoquinoline alkaloid extracted from the Chinese herb, Coptis rhizome, which exhibits numerous biological effects on gastrointestinal disorders. However, the effects of berberine on SAP‑induced cognitive impairments remain unknown. The present study aimed to investigate the effects of berberine on cognitive impairments associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Berberine, a common extract found in these two drugs, has anti‐apoptotic properties, anti‐neuroinflammatory effects, and mitoprotective effects (Kalalian‐Moghaddam et al., 2013; Ou et al., 2018; Zhao et al., 2019). CR has been shown to contain more berberine than PB (Anetai, 1994; Anetai et al., 1987), which may result in a stronger effect on the reduction in drebrin cluster densities for CR compared with PB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Berberine, a common extract found in these two drugs, has anti‐apoptotic properties, anti‐neuroinflammatory effects, and mitoprotective effects (Kalalian‐Moghaddam et al., 2013; Ou et al., 2018; Zhao et al., 2019). CR has been shown to contain more berberine than PB (Anetai, 1994; Anetai et al., 1987), which may result in a stronger effect on the reduction in drebrin cluster densities for CR compared with PB.…”
Section: Discussionmentioning
confidence: 99%
“…Nobiletin, a citrus flavonoid, diosgenin, a well‐known steroidal sapogenin from wild yam, and tenuifolin, a bio‐active terpenoid from Polygala tenuifolia , have been well‐studied, especially in relation to AD (Liu et al., 2015; Lv et al., 2009; Matsuzaki et al., 2006; Nakajima & Ohizumi, 2019; Onozuka et al., 2008; Tohda et al., 2012; Wang, Jin, et al., 2019; Youn et al., 2019). Uncaria Hook (UH), Bezoar Bovis (BB), Coptis Rhizome (CR), Phellodendron Bark (PB) and Polygala Root (PR) are also well‐known for their effects on cognitive dysfunction and AD (Cai et al., 2013; Hu et al., 2014; Kalalian‐Moghaddam et al., 2013; Kanno et al., 2013; Ou et al., 2018; Park et al., 2002; Zhao et al., 2016, 2019). CR, PB and PR have previously been examined in clinical studies (Linn et al., 2012; Shin et al., 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, rodent models show hippocampal TNF/TNFR1 activity regulates hindpaw neuropathic pain (52,58). Since acute pancreatitis promotes a systemic inflammatory response in both humans and rodents (69,70), including TNF upregulation within the hippocampus (71), we sought to determine whether our model of pancreatitis promotes an inflammatory state within the hippocampus that could play a role in the development of peripheral hindpaw mechanical hypersensitivity.…”
Section: Selective Inhibition Of Soltnf Using Xpro1595 Attenuates Cermentioning
confidence: 99%
“…Mizunuma et al [103] proposed a model that established the intraperitoneal route with L-arginine hydrochloride. Several modifications of this model showed that higher doses can produce high mortality, repeated doses promote necrosis, and reduced doses may delay the time of onset of AP [73,74,104]. Table 3 summarizes the most commonly used doses of L-arginine when administered by the intraperitoneal route.…”
Section: Murine Models: a Practical Overviewmentioning
confidence: 99%